The Vocabulary of Emotions Test (VET) : psychometric properties of the Serbian version - Altaras Dimitrijević, Ana (Array, 2020)
Considering the necessity to broaden the range of valid emotional intelligence (EI) measures, this study further examined the psychometric properties of the Vocabulary of Emotions Test (VET; Takšić, Harambašić, & Velemir, 2003). Participants were 333 university students (75.4% female) from Serbia, 245 studying education sciences or humanities, and 88 pursuing natural/technical sciences. All were administered the Serbian version of the VET and two standard tests of verbal intelligence (VI) and asked to report their average grade. The VET had good internal consistency (α = .83) and correlated positively with both measures of VI (r = .37 and .45), as with participants’ grades (r = .20). Significant group differences emerged on the VET, but not the two VI tests, with female participants and the Education Sciences/Humanities group scoring higher than their respective counterparts. A hierarchical regression analysis with VI (Step 1) and VET scores (Step 2) as predictors, and grades as the criterion, yielded a significant model (R 2 = .04) with emotional vocabulary explaining additional variance over VI (ΔR 2 = .02) and surfacing as the only independent predictor (β = .18) of academic achievement. Further analyses showed emotional vocabulary to incrementally predict achievement in education sciences and humanities (ΔR 2 = .03, β = .19), but not in natural/technical sciences, in which context neither VI nor emotional vocabulary were statistically significant predictors of students’ grades. The current results are interpreted as promising evidence on the reliability and validity of the Serbian VET, encouraging further use of this instrument in EI research.